Identifying Common Data Elements to Achieve Injury-related Health Equity Across the Lifespan: A Consensus-Driven Approach - Kelsey M. Conrick; Brianna Mills; Molly Fuentes; Janessa M. Graves; Christopher St. Vil; Monica S. Vavilala; Eileen M. Bulger; Saman Arbabi; Ali Rowhani-Rahbar; Megan Moore (Health Equity)
Background: Limited availability and poor quality of data in medical records and trauma registries impede progress to achieve injury-related health equity across the lifespan. Methods: We used a Nominal Group Technique (NGT) in-person workgroup and a national web-based Delphi process to identify common data elements (CDE) that should be collected. Results: The 12 participants in the NGT workgroup and 23 participants in the national Delphi process identified 10 equity-related CDE and guiding lessons for research on collection of these data. Conclusions: These high-priority CDE define a detailed, equity-oriented approach to guide research to achieve injury-related health equity across the lifespan.